CITY BRANDING BERBASIS LOCAL WISDOM DALAM KAMPANYE “BETTER BANYUMAS” - Ascharisa Mettasatya Afrilia (Metacommunication, 2018)
Branding strategies in the context of marketing are important. Not only to label a product to be more valuable, a branding strategy is also important to position the product in the scope of the market itself. Increasingly, branding strategies also began to be applied to many lines. The existence of a place is also considered important to adopt a branding strategy to define itself in regional character. This definition is known as the city branding.. Banyumas, as one of the cities in the Central Java region, realizes the importance of city branding to instill a philosophy of local wisdom with the campaign that is promoted "Better Banyumas". The campaign is a form of city branding that aims to introduce Banyumas to all internal and external communities. This paper was analyzed using descriptive qualitative methods. Based on the results and discussion it is known that the awareness of the valuesof local wisdom which is the basis of strength for Banyumas culture has been maintained in a more universal way. Thus, public acceptance of the valuesof local wisdom is maintained and in accordance with the development of the millennial era. It can be concluded that the "Better Banyumas" campaign movement is a great hope in realizing a better society that loves and cares for Banyumas. Through this city branding movement, Banyumas District Government strives to implement city marketing strategies based on local wisdom with broader, faster, and more targeted targets.Keywords:  City Branding, Better Banyumas, Marketing Communication, Public Relations.